2013
DOI: 10.1103/physrevb.88.075302
|View full text |Cite
|
Sign up to set email alerts
|

Band offsets between ZnGeN2, GaN, ZnO, and ZnSnN2and their potential impact for solar cells

Abstract: The band offsets between the Zn-IV-N2 nitrides, ZnGeN2 and ZnSnN2, and two other closely lattice matched semiconductors, ZnO and GaN, are calculated using density functional theory calculations including quasiparticle corrections. The interface dependence as well as the role of strain are investigated. A staggered type-II alignment is found between ZnGeN2, GaN and ZnO with ZnO having the lower and ZnGeN2 having the higher valence band maximum. The potential benefits of this alignment for photovoltaic applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 23 publications
7
45
0
Order By: Relevance
“…The band offsets among the Zn‐IV‐N 2 compounds and GaN and ZnO were reported by Punya et al Recently, the band‐offsets of ZnSnN 2 to GaN were also reported by Wang et al and Arca et al The work by Wang et al provided a quite small value of only 0.39 eV, while our calculations gave a value of 1.4 eV and Arca et al gave a value of 1.0–1.4 eV based on measurements of the position of the valence band maximum (VBM) in ZnSnN 2 relative to the vacuum level and literature values of the same in GaN. We note here that in ref.…”
Section: Band Offsetssupporting
confidence: 77%
“…The band offsets among the Zn‐IV‐N 2 compounds and GaN and ZnO were reported by Punya et al Recently, the band‐offsets of ZnSnN 2 to GaN were also reported by Wang et al and Arca et al The work by Wang et al provided a quite small value of only 0.39 eV, while our calculations gave a value of 1.4 eV and Arca et al gave a value of 1.0–1.4 eV based on measurements of the position of the valence band maximum (VBM) in ZnSnN 2 relative to the vacuum level and literature values of the same in GaN. We note here that in ref.…”
Section: Band Offsetssupporting
confidence: 77%
“…15 However, measurement of the band gap by photoluminescence excitation spectroscopy 19 of material that looked wurtzitic in x-ray diffraction gave a gap in close agreement with accurately predictive quasiparticle band structure calculations for perfectly ordered P na2 1 crystals, using experimentally determined lattice parameters. 13,26 The main question we address in this paper is how to reconcile these seemingly contradictory observations.…”
Section: Introductionmentioning
confidence: 99%
“…11 Some are predicted to have important potential for several applications in optoelectronics, from solid-state lighting 12 to photovoltaics. 13 The synthesis of ZnSnN 2 in particular has fueled interest in its use for solar photovoltaics, especially because this material is composed solely of earthabundant elements. [14][15][16][17][18][19][20][21] As is the case for the zincblendebased ternaries, the type of ordering and the possibility of order-disorder transitions in the wurtzite-based ternaries are of fundamental as well as practical interest.…”
Section: Introductionmentioning
confidence: 99%
“…Still, noticeable errors prevail in the band gaps and IPs, in particular, of wide gap materials [21,40]. The GW approximation to many-body perturbation theory (MBPT) [55,56] in general predicts the band structure of solids more accurately and has also been applied to the evaluation of IPs and EAs [19][20][21][22], interfacial band offsets [26,[57][58][59][60], and branch point energies [15,22]. We have recently reported that the GW approximation suffers from sizable self-interaction errors not only for localized states, as pointed out previously [61,62], but also for extended states in the valence and conduction bands of most semiconductors [21].…”
Section: Introductionmentioning
confidence: 99%